2019
DOI: 10.1177/0162643419878146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Computerized Instruction on Mastery and Generalized Use of Commas Strategies by Students With LD

Abstract: The effects of an interactive multimedia (IM) software program for teaching comma strategies to students with learning disabilities (LD) were determined with regard to the students’ sentence-editing and sentence-construction skills. Students with LD at the middle-school and high-school levels were randomly selected in their intact cohorts for the experimental and control groups. Results showed that the experimental students completed the software program and readily learned information about and mastered the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Clearly, the multimedia instruction represented here and in other studies (e.g., Lancaster et al, 2002, 2006, 2009; Schumaker, Fisher, & Walsh, 2019; Schumaker, Walsh, & Fisher, 2019) is a different type of instruction than what is typically used in today’s schools. Classrooms need to be equipped with computers that can run these very interactive programs (Lancaster et al, 2005, 2007; Schumaker, 2013; Schumaker & Sheldon, 2009, 2010), as well as with printers that students can use to print out their products. Nevertheless, interactive programs are required since students need high levels of interactivity and feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the multimedia instruction represented here and in other studies (e.g., Lancaster et al, 2002, 2006, 2009; Schumaker, Fisher, & Walsh, 2019; Schumaker, Walsh, & Fisher, 2019) is a different type of instruction than what is typically used in today’s schools. Classrooms need to be equipped with computers that can run these very interactive programs (Lancaster et al, 2005, 2007; Schumaker, 2013; Schumaker & Sheldon, 2009, 2010), as well as with printers that students can use to print out their products. Nevertheless, interactive programs are required since students need high levels of interactivity and feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have developed and tested some IM programs for teaching writing strategies. For example, Schumaker, Fisher, & Walsh (2019) tested an IM program for teaching Punctuation Strategies (Schumaker & Sheldon, 2010), and Schumaker, Walsh, & Fisher (2019) tested a similar program for teaching Commas Strategies (Schumaker & Sheldon, 2009). The instructional methodology used in both IM programs was Strategic Instruction (Ellis et al, 1991; Schumaker & Deshler, 2006).…”
mentioning
confidence: 99%
“…Some researchers have shown that these instructional methods can be incorporated into interactive multimedia (IM) programs to teach academic skills (e.g., Lancaster et al, 2006Lancaster et al, , 2009Schumaker, 2020;Schumaker et al, 2019aSchumaker et al, , 2019b) and social skills. With regard to social skills, Lancaster et al (2002) conducted a study whereby students with learning disabilities (LD) were taught self-advocacy skills to be used in Individualized Education Program (IEP) meetings with an IM program.…”
Section: Multimedia Instruction As a Solutionmentioning
confidence: 99%